Enhanced natural graphite composite film and preparation method thereof

Through plasma treatment and hot pressing process, nano silicon carbide and graphene oxide dispersion are combined to form a graphene-natural graphite composite film, solving the problem of insufficient performance in high-end applications of traditional natural graphite films and achieving higher thermal conductivity, mechanical strength and chemical stability.

CN119767635AActive Publication Date: 2025-04-04JIANGSU HANHUA TM TECHNOLOGY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411949477.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Traditional natural graphite films are difficult to meet the requirements of higher thermal conductivity, better mechanical strength and more stable chemical performance in high-end applications, and the interface bonding force between the graphene layer and natural graphite may be weak, especially under high temperature or repeated thermal cycling conditions, layering or performance degradation may occur.

Method used

The natural graphite film is activated by plasma treatment, and the nano silicon carbide dispersion and graphene oxide dispersion are prepared, and sprayed and coated on the surface of the natural graphite film respectively. The low-temperature heat treatment and low-temperature reduction treatment are used to form a graphene-natural graphite composite film, and its mechanical strength and thermal conductivity are improved through hot pressing treatment.

Benefits of technology

The thermal conductivity, mechanical strength and chemical stability of the composite film are significantly improved, forming a tight interface structure, enhancing the bonding force between the graphene layer and the natural graphite film, meeting the needs of high-end applications, while maintaining low cost and easy processing characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119767635A_ABST
    Figure CN119767635A_ABST
Patent Text Reader

Abstract

The invention discloses an enhanced natural graphite composite film and a preparation method thereof, and the preparation method of the natural graphite composite film comprises the following steps: carrying out plasma treatment on a natural graphite film to activate the surface to obtain a pretreated natural graphite film; preparing nano silicon carbide dispersion liquid, uniformly spraying the nano silicon carbide dispersion liquid on the surface of the pretreated natural graphite film, and performing low-temperature heat treatment and drying to obtain a natural graphite film with an interface enhancement layer; preparing a graphene oxide dispersion liquid, coating the graphene oxide dispersion liquid on the surface of the natural graphite film with the interface enhancement layer, and performing low-temperature reduction treatment to obtain a graphene-natural graphite composite film; and placing the graphene-natural graphite composite film in a pressing mechanism, and carrying out hot pressing treatment to obtain the enhanced natural graphite composite film. By reasonably designing a preparation process and selecting materials, the performance of the enhanced natural graphite composite film is improved, and the enhanced natural graphite composite film shows excellent thermal conductivity, chemical stability, mechanical strength and heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphite film materials, and in particular to an enhanced natural graphite composite film and a preparation method thereof. Background Art

[0002] As an excellent thermal conductive material, natural graphite has the characteristics of high thermal conductivity, light weight and low cost, and has broad application prospects in the field of heat dissipation. However, with the rapid development of modern electronic technology, the performance requirements of materials are increasing day by day. Traditional natural graphite films can no longer meet the needs of high-end applications in some aspects, such as higher thermal conductivity, better mechanical strength and more stable chemical properties.

[0003] As a new type of two-dimensional material, graphene has extremely high thermal conductivity (theoretical value is up to 5000W / m·K) and excellent mechanical strength. Combining graphene with natural graphite film can not only make up for the shortcomings of natural graphite film in grain boundary defects and structural uniformity, but also enhance its overall mechanical properties. Especially in the context of electronic devices requiring thermal conductive materials to be light, thin and efficient, this composite technology has broad application prospects.

[0004] Chinese patent CN 111526695A discloses a double-sided graphene heat dissipation film and preparation method, the steps are as follows: soaking graphene oxide in water and performing ultrasonic stirring to form a graphene oxide solution; laminating the back of a natural graphite coil to a PET double-sided silicone film to form a natural graphite back adhesive coil; coating the graphene oxide solution on the front of the natural graphite coil, and continuously drying and reducing to form an upper graphene layer; peeling off the PET double-sided silicone film in the obtained single-sided graphene heat dissipation film coil; coating the graphene oxide solution on the back of the natural graphite layer, and continuously drying and reducing to form a lower graphene layer, thereby preparing a double-sided graphene heat dissipation film coil. The invention adopts the method of coating and drying and reducing the graphene oxide solution, and the process flow is simple and easy to operate; however, the graphene layer is formed by coating and reducing the graphene oxide, and its interface bonding force with the natural graphite may be weak, especially under high temperature or repeated thermal cycle conditions, and delamination or performance degradation may occur. Summary of the invention

[0005] Based on the problems existing in the background technology, the present invention provides an enhanced natural graphite film-graphene composite film material and a preparation method thereof, which not only retains the original advantages of natural graphite film but also can significantly improve the performance by adding a graphene layer. The composite material needs to have higher thermal conductivity, enhanced mechanical strength and good chemical stability, while maintaining low cost and easy processing characteristics.

[0006] The present invention is implemented by the following technical solutions:

[0007] The present invention provides a method for preparing an enhanced natural graphite composite film, comprising the following steps:

[0008] S1. The natural graphite film is subjected to plasma treatment to activate the surface to obtain a pretreated natural graphite film;

[0009] S2. Prepare a nano-silicon carbide dispersion, spray the nano-silicon carbide dispersion evenly on the surface of the pretreated natural graphite film, heat treat and dry at low temperature to obtain a natural graphite film with an interface enhancement layer;

[0010] S3. preparing a graphene oxide dispersion, coating the graphene oxide dispersion on the surface of the natural graphite film with an interface enhancement layer, and performing a low-temperature reduction treatment to obtain a graphene-natural graphite composite film;

[0011] S4. placing the graphene-natural graphite composite film in a pressing mechanism and performing a hot pressing treatment to obtain an enhanced natural graphite composite film.

[0012] Furthermore, in step S1, the plasma treatment is performed using argon gas at a low pressure of 50-100 Pa and a power of 100-200 W for 15-30 min.

[0013] Plasma treatment makes the surface of the natural graphite film more active, which helps the bonding between the graphene layer and the natural graphite film and improves the overall stability of the composite film. In addition, the natural graphite film after plasma treatment has better mechanical strength and wear resistance, which can increase the long-term service life of the composite film.

[0014] Furthermore, in step S2, the concentration of the nano-silicon carbide dispersion is 0.5-2 mg / mL, the solvent is ethanol, and the coating method is spin coating or spray coating.

[0015] Nano-silicon carbide has excellent thermal conductivity and chemical stability. It can effectively adjust the interface between natural graphite film and graphene layer, form a tighter interface structure, improve the bonding force between natural graphite film and graphene layer, optimize the thermal conductivity between the two, and reduce the impact of thermal expansion.

[0016] Furthermore, the temperature of the low temperature heat treatment and drying in step S2 is 40-60°C.

[0017] Furthermore, in step S3, the concentration of the graphene oxide dispersion is 0.5-2 mg / mL, and the solvent is deionized water.

[0018] The reduction process converts graphene oxide into graphene, restoring its excellent thermal conductivity and further improving the thermal conductivity of the composite film. Graphene oxide forms a stronger chemical bond through the interface between the reduced graphene and nano-silicon carbide, improving the bonding force between the graphene layer and the natural graphite film, and increasing the mechanical strength and stability of the composite film.

[0019] Furthermore, the graphene oxide dispersion in step S3 also includes vitamin C, silane coupling agent KH550 and polyvinyl alcohol; the concentration of vitamin C is 0.01-0.03 mg / mL, the concentration of silane coupling agent KH550 is 0.01-0.03 mg / mL, and the concentration of polyvinyl alcohol is 0.02-0.05 mg / mL.

[0020] In the reduction process, vitamin C acts as a reducing agent, which can effectively reduce the oxygen functional groups in graphene oxide, while maintaining the high-quality structure of graphene and avoiding over-reduction or degradation. The synergistic effect of silane coupling agent KH550 and polyvinyl alcohol further regulates the interfacial chemical properties and establishes a tighter interfacial bonding network at the molecular scale.

[0021] Furthermore, in step S3, the temperature of the low-temperature reduction treatment is 120-135° C., and the treatment time is 1-2 h.

[0022] Furthermore, in step S4, the temperature of the hot pressing treatment is 150-200° C., the pressure is 10-20 MPa, and the treatment time is 15-30 min.

[0023] The cam is provided with a plurality of springs, each of which is provided with a plurality of springs, each of which is provided with a plurality of springs, and the plurality of springs are provided with a plurality of springs.

[0024] Hot pressing treatment uses high temperature and high pressure to rearrange and combine the molecules in the composite film, further optimizing the density, mechanical strength and thermal conductivity of the film; hot pressing not only promotes the adhesion of the graphene layer, but also improves the overall stability of the composite film.

[0025] The second aspect of the present invention provides an enhanced natural graphite composite film, which is prepared by the above method and includes a natural graphite layer and a graphene layer; wherein the thickness of the natural graphite layer is 0.025-0.25 mm, and the thickness of the graphene layer is 0.01-0.025 mm.

[0026] Beneficial effects of the present invention:

[0027] 1. The present invention combines natural graphite film and graphene, and finally forms an enhanced natural graphite composite film with excellent performance through hot pressing. Graphene has a very high thermal conductivity due to its unique two-dimensional structure and atomic-level thickness, which can significantly improve the vertical thermal conductivity of the composite film. The addition of graphene greatly improves the thermal conductivity of the composite film, and can more effectively transfer heat under high heat load to avoid local overheating. The addition of the graphene layer enables the composite film to better disperse and transfer stress under stress, avoid local stress concentration of the composite film, and improve the strength and toughness of the composite film. In addition, graphene itself has a strong antioxidant ability, can resist common chemical corrosion, and maintain its excellent thermal conductivity and structural stability. The graphene layer forms an effective barrier in the composite film to prevent the membrane material from being degraded by environmental influences during long-term use.

[0028] 2. Nano-SiC itself has a high thermal conductivity. As an interface enhancement layer, it alleviates the thermal expansion difference between graphene and natural graphite, and improves the thermal conductivity efficiency of the composite film. The micron-scale size and good dispersion of nano-SiC enable it to provide a more uniform heat conduction path, which helps to improve the thermal conductivity of the overall composite film.

[0029] 3. After the graphene layer and the natural graphite film are tightly combined through the hot pressing process, a continuous and efficient heat conduction channel is formed, which further improves the thermal conductivity of the composite film. The thermal conductivity of the composite film has been significantly improved, which can meet the needs of high thermal conductivity applications, such as electronic equipment heat dissipation materials, thermal management films and other fields.

[0030] 4. In the low-temperature reduction stage, vitamin C reduces the oxidized functional groups of graphene oxide to graphene through its reducing hydrogen atoms and maintains the structural integrity of the graphene layer. The amino group in the silane coupling agent KH550 can promote the chemical bonding between graphene and nano-silicon carbide, thereby improving the interfacial bonding between the two. Polyvinyl alcohol, as a bonding agent, further enhances the stability of the graphene layer and the toughness of the composite film. The hydrophilicity and film-forming properties of polyvinyl alcohol can help improve the uniformity of the graphene film while reducing cracks or unevenness that may occur in the graphene layer during the reduction process. The combined use of silane coupling agent KH550 and polyvinyl alcohol can not only improve the interfacial bonding between the graphene layer and silicon carbide, but also improve the structural stability and thermal conductivity of the graphene layer. Silane coupling agent KH550 provides a chemical bonding pathway, while polyvinyl alcohol enhances the uniformity of the graphene film through bonding and film-forming effects.

[0031] 5. The process steps of the present invention are relatively simple and efficient. The selection of the low-temperature reduction process can not only avoid graphene damage at high temperatures, but also reduce energy consumption and improve production efficiency. The combination of plasma treatment and hot pressing process can not only improve the performance of the composite film, but also reduce additional processing steps to a certain extent, improve production efficiency and reduce production costs. These steps can be easily implemented in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings are used to provide further explanation of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0033] Figure 1 It is a cross-sectional schematic diagram of the pressing mechanism in the present invention;

[0034] Figure 2 A three-dimensional diagram of some structures in the pressing mechanism of the present invention Figure 1 ;

[0035] Figure 3 A three-dimensional diagram of some structures in the pressing mechanism of the present invention Figure 2 ;

[0036] Figure 4 A three-dimensional diagram of some structures in the pressing mechanism of the present invention Figure 3 ;

[0037] Figure 5 This is a schematic diagram of the structure of the natural graphite composite membrane of the present invention;

[0038] In the figure: 1. Pressing frame; 2. Bracket plate; 3. Telescopic cylinder 1; 4. Driving motor; 5. Bracket body; 6. Return spring; 7. Pressing groove; 8. Telescopic cylinder 2; 9. Pressing plate; 10. Heating head; 11. Chamfer; 12. Through hole; 13. Pressing down insulation chamber; 14. Threaded rod; 15. Anti-slip part; 16. Oblique pressing end. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0040] In the examples and comparative examples of the present invention, in the prepared composite film, the thickness of the natural graphite layer is 0.25 mm, and the thickness of the graphene layer is 0.025 mm.

[0041] Example 1

[0042] A method for preparing an enhanced natural graphite composite film comprises the following steps:

[0043] S1. The natural graphite film was subjected to plasma treatment to activate the surface, and high-purity argon was used for 30 min at a low pressure of 50 Pa and a power of 200 W to obtain a pretreated natural graphite film;

[0044] S2. Prepare a nano-silicon carbide dispersion (solvent is ethanol) with a concentration of 1 mg / mL, spray the nano-silicon carbide dispersion evenly on the surface of the pretreated natural graphite film, heat treat and dry at 50 ° C to obtain a natural graphite film with an interface enhancement layer;

[0045] S3. Prepare a graphene oxide dispersion, using deionized water as a solvent, the concentration of the graphene oxide dispersion is 2 mg / mL, the concentration of vitamin C is 0.02 mg / mL, the concentration of silane coupling agent KH550 is 0.02 mg / mL, and the concentration of polyvinyl alcohol is 0.04 mg / mL; the graphene oxide dispersion is applied on the surface of the natural graphite film with an interface enhancement layer by spin coating, and the graphene oxide dispersion is subjected to low-temperature reduction treatment at 130°C for 1.5 h to obtain a graphene-natural graphite composite film;

[0046] S4. Place the graphene-natural graphite composite film in a pressing mechanism and perform hot pressing treatment. The hot pressing treatment temperature is 180° C., the pressure is 15 MPa, and the treatment time is 20 min to obtain an enhanced natural graphite composite film.

[0047] Example 2

[0048] In this embodiment, step S3 prepares a graphene oxide dispersion, using deionized water as a solvent, the concentration of the graphene oxide dispersion is 1.5 mg / mL, the concentration of vitamin C is 0.02 mg / mL, the concentration of silane coupling agent KH550 is 0.02 mg / mL, and the concentration of polyvinyl alcohol is 0.03 mg / mL; the remaining steps are the same as in Example 1.

[0049] Comparative Example 1

[0050] In this comparative example, the step of uniformly spraying the nano silicon carbide dispersion on the surface of the pretreated natural graphite film is not included, that is, the graphite oxide dispersion is directly coated on the natural graphite film after pretreatment, and the remaining steps are the same as those in Example 1.

[0051] Comparative Example 2

[0052] In this comparative example, step S3 prepares a graphene oxide dispersion, uses deionized water as a solvent, the concentration of the graphene oxide dispersion is 2 mg / mL, vitamin C, silane coupling agent KH550 and polyvinyl alcohol are not included, and the remaining steps are the same as in Example 1.

[0053] Comparative Example 3

[0054] In this comparative example, step S3 prepares a graphene oxide dispersion, uses deionized water as a solvent, the concentration of the graphene oxide dispersion is 2 mg / mL, the concentration of vitamin C is 0.02 mg / mL, silane coupling agent KH550 and polyvinyl alcohol are not included, and the remaining steps are the same as in Example 1.

[0055] Comparative Example 4

[0056] In this comparative example, in step S3, a graphene oxide dispersion is prepared, deionized water is used as a solvent, the concentration of the graphene oxide dispersion is 2 mg / mL, the concentration of vitamin C is 0.02 mg / mL, the concentration of the silane coupling agent KH550 is 0.02 mg / mL, polyvinyl alcohol is not included, and the remaining steps are the same as in Example 1.

[0057] Comparative Example 5

[0058] In this comparative example, step S1 is to clean the natural graphite film with ethanol and deionizer to obtain a pretreated natural graphite film, and the remaining steps are the same as those in Example 1.

[0059] Comparative Example 6

[0060] This comparative example is a natural graphite film.

[0061] Test example

[0062] The performance of the natural graphite composite films prepared in Examples 1-2 and Comparative Examples 1-5 and the natural graphite film in Comparative Example 6 were tested.

[0063] Thermal diffusivity test: The thermal diffusivity of natural graphite composite film was tested using NETZSCH LFA467. The test temperature was set at room temperature (25°C), the voltage was 260V, the sampling time was 30ms, the detection area was 14mm, and the test sample size was a disc with a diameter of 2.54cm.

[0064] Density test: calculated by weight and size method;

[0065] Thermal conductivity: calculated based on thermal diffusivity, density and specific heat capacity (0.85 J / g*K);

[0066] The test results are shown in Table 1.

[0067] Table 1

[0068]

[0069]

[0070] As can be seen from the data in Table 1, the natural graphite composite film prepared in the embodiment of the invention has excellent thermal conductivity. After the natural graphite layer and the graphene layer are closely combined with the interface enhancement layer nano silicon carbide layer by hot pressing process, a continuous and efficient heat conduction channel is formed, which improves the heat conduction efficiency of the composite film. There is no nano silicon carbide interface enhancement in Comparative Example 1. Nano silicon carbide, as an interface enhancement, can improve the vertical thermal conductivity of the composite film, especially in terms of the interface bonding of the film. Removing nano silicon carbide weakens the interface heat transfer ability, the interface bonding force is reduced, and the heat transfer path is affected, so that the thermal diffusion coefficient of the composite film is significantly reduced. In Comparative Example 2, vitamin C, silane coupling agent KH550 and polyvinyl alcohol are not added when preparing graphene oxide dispersion liquid, which means that the degree of interface chemical bond and functional modification is weakened, thereby affecting the dispersibility and interface bonding of nano silicon carbide and graphene oxide. Lack of these auxiliary agents, the reduction degree of graphene oxide may not be as good as Example 1, resulting in poor dispersion and uniformity of the graphene layer in the composite film, resulting in a slight decrease in the density of the composite film, and even the presence of tiny pores or interface inhomogeneous regions. In Example 1, vitamin C promotes the reduction of graphene oxide, and silane coupling agent KH550 and polyvinyl alcohol assist the reduced graphene to form chemical bonds with the nano-silicon carbide interface, enhancing the thermal conductivity between the graphene layer and the natural graphite layer, while the lack of these auxiliary agents in Comparative Example 2 will result in incomplete reduction of graphene oxide, and the combination of the graphene layer and the natural graphite layer is not as tight as in Example 1, resulting in poor thermal conductivity between the interfaces, and the thermal diffusion coefficient of the composite film is reduced. In Comparative Example 3, the graphene oxide dispersion does not include silane coupling agent KH550 and polyvinyl alcohol, and in Comparative Example 4, the graphene oxide dispersion does not include polyvinyl alcohol, and the thermal conductivity between the interface of the graphene layer and the natural graphite layer is poor, and the thermal diffusion coefficient of the composite film is reduced. In comparative example 5, natural graphite film is only treated with ethanol and deionized water for cleaning, rather than activating the surface by plasma treatment. Plasma treatment can effectively remove organic matter, oxides and impurities on the surface of natural graphite film, increase the active groups on its surface, and improve the surface roughness and hydrophilicity of natural graphite film. This helps to enhance the adhesion of materials such as graphene oxide and nano silicon carbide, so that they can be more evenly distributed on the surface of graphite film, and finally form a more compact composite film. Although ethanol and deionized water cleaning can remove impurities on the surface of graphite film, surface active groups will not be increased and surface structure will not be improved, therefore, the surface activity of natural graphite film is relatively low, and the adhesion performance of nano silicon carbide and graphene will be reduced, and the interface bonding is not as good as the treatment effect in Example 1, resulting in poor compactness of composite film, discontinuity in heat conduction path, thereby increasing heat conduction resistance, reducing thermal diffusion coefficient.

[0071] Example 2

[0072] Based on Example 1, please refer to Figure 1-Figure 5The pressing mechanism includes: a pressing frame 1, which is a frame with front and rear openings, a bracket plate 2 is fixedly connected to the inner wall of the pressing frame 1, a telescopic cylinder 2 8 is fixedly arranged on the top of the inner wall of the pressing frame 1, a pressing groove 7 is arranged at the bottom of the inner wall of the pressing frame 1, a through hole 12 is arranged at the center of the bracket plate 2, the movable end of the telescopic cylinder 2 8 passes through the through hole 12 and is fixedly provided with a pressing plate 9, a heating head 10 is installed at the bottom of the pressing plate 9, a fixed end of the telescopic cylinder 3 is fixedly connected to the bottom of the bracket plate 2, a movable end of the telescopic cylinder 3 is fixedly connected to the bracket body 5, and the bracket body 5 is connected to A return spring 6 is provided between the bottom of the inner wall of the pressed frame 1, a downward pressure insulation chamber 13 is provided in the middle of the bracket body 5, and a plurality of groups of drive motors 4 are installed on the vertical sections on both sides of the bracket body 5. The output end of each group of drive motors 4 is fixedly connected with a threaded rod 14, and the end of the threaded rod 14 away from the drive motor 4 is rotatably connected to the outer wall of the downward pressure insulation chamber 13, and the anti-slip component 15 is movably sleeved on the outer wall of the threaded rod 14, and the anti-slip component 15 and the threaded rod 14 are connected by threads, and the top of the anti-slip component 15 extends toward the direction close to the downward pressure insulation chamber 13 to form an oblique pressure end 16.

[0073] The working principle and beneficial effects of the above scheme are as follows: when in use, after placing the graphene-natural graphite composite film in the pressing groove 7 of the pressing frame 1, the telescopic cylinder 3 is started to push the bracket body 5 down until the heat preservation cavity 13 is pressed down to enter the pressing groove 7 and fit with the graphene-natural graphite composite film therein, and then pressure is applied to achieve the effect of preliminary pressing. Subsequently, the telescopic cylinder 2 8 is started to push the pressing plate 9 down until the heating head 10 enters the downward pressure insulation chamber 13, and the driving motor 4 is started to drive the threaded rod 14 to rotate, so that the two sets of anti-slip parts 15 move toward the direction close to the downward pressure insulation chamber 13 until the oblique pressure end 16 of the anti-slip part 15 coincides with the chamfer 11 of the pressing plate 9, thereby ensuring stability during the pressing process. As the temperature of the heating head 10 rises until the temperature of the entire downward pressure insulation chamber 13 rises to the required 150-200°C and with the cooperation of the telescopic cylinder 1 3 and the telescopic cylinder 2 8, the pressure on the graphene-natural graphite composite film is ensured to be between 10-20MPa, and an enhanced natural graphite composite film is obtained after 20 minutes.

[0074] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an enhanced natural graphite composite film, characterized in that: The following steps are involved: S1. The natural graphite film is subjected to plasma treatment to activate the surface to obtain a pretreated natural graphite film; S2. Prepare a nano-silicon carbide dispersion, spray the nano-silicon carbide dispersion evenly on the surface of the pretreated natural graphite film, heat treat and dry at low temperature to obtain a natural graphite film with an interface enhancement layer; S3. preparing a graphene oxide dispersion, coating the graphene oxide dispersion on the surface of the natural graphite film with an interface enhancement layer, and performing a low-temperature reduction treatment to obtain a graphene-natural graphite composite film; S4. placing the graphene-natural graphite composite film in a pressing mechanism and performing a hot pressing treatment to obtain an enhanced natural graphite composite film.

2. The method for preparing the enhanced natural graphite composite film according to claim 1, characterized in that: In step S1, the plasma treatment is performed using argon gas at a low pressure of 50-100 Pa and a power of 100-200 W for 15-30 minutes.

3. The method for preparing the enhanced natural graphite composite film according to claim 1, characterized in that: The concentration of the nano-silicon carbide dispersion in step S2 is 0.5-2 mg / mL, and the solvent is ethanol.

4. The method for preparing the enhanced natural graphite composite film according to claim 1, characterized in that: The temperature of the low temperature heat treatment and drying in step S2 is 40-60°C.

5. The method for preparing the enhanced natural graphite composite film according to claim 1, characterized in that: In step S3, the concentration of the graphene oxide dispersion is 0.5-2 mg / mL, the solvent is deionized water, and the coating method is spin coating or spray coating.

6. The method for preparing the enhanced natural graphite composite film according to claim 1, characterized in that: The graphene oxide dispersion in step S3 also includes vitamin C, silane coupling agent KH550 and polyvinyl alcohol; the concentration of vitamin C is 0.01-0.03 mg / mL, the concentration of silane coupling agent KH550 is 0.01-0.03 mg / mL, and the concentration of polyvinyl alcohol is 0.02-0.05 mg / mL.

7. The method for preparing the enhanced natural graphite composite film according to claim 1, characterized in that: The temperature of the low-temperature reduction treatment in step S3 is 120-135° C., and the treatment time is 1-2 hours.

8. The method for preparing the enhanced natural graphite composite film according to claim 1, characterized in that: The temperature of the hot pressing treatment in step S4 is 150-200° C., the pressure is 10-20 MPa, and the treatment time is 15-30 min.

9. The method for preparing the enhanced natural graphite composite film according to claim 1, characterized in that: The pressing mechanism comprises: a pressing frame (1), the pressing frame (1) being a frame with front and rear openings, a support plate (2) being fixedly connected to the inner wall of the pressing frame (1), a telescopic cylinder (2) (8) being fixedly arranged at the top of the inner wall of the pressing frame (1), a pressing groove (7) being arranged at the bottom of the inner wall of the pressing frame (1), a through hole (12) being arranged at the center of the support plate (2), a movable end of the telescopic cylinder (2) (8) passing through the through hole (12) and being fixedly arranged with a pressing plate (9), a heating head (10) being installed at the bottom of the pressing plate (9), a fixed end of the telescopic cylinder (3) (1) being fixedly connected to the bottom of the support plate (2), a movable end of the telescopic cylinder (3) (1) being fixedly connected to the support body (5), and the support body (5 ) and the bottom of the inner wall of the pressing frame (1), a return spring (6) is provided between the bracket body (5), a downward pressure insulation chamber (13) is provided in the middle of the bracket body (5), and a plurality of groups of drive motors (4) are installed on the vertical sections on both sides of the bracket body (5), and the output end of each group of drive motors (4) is fixedly connected to a threaded rod (14), and the end of the threaded rod (14) away from the drive motor (4) is rotatably connected to the outer wall of the downward pressure insulation chamber (13), and the anti-slipping member (15) is movably sleeved on the outer wall of the threaded rod (14), and the anti-slipping member (15) and the threaded rod (14) are connected by threads, and the top of the anti-slipping member (15) extends in a direction close to the downward pressure insulation chamber (13) to form an oblique pressure end (16).

10. An enhanced natural graphite composite film, characterized in that: The method is prepared by any one of claims 1 to 9, comprising a natural graphite layer (17) and a graphene layer (18), wherein the thickness of the natural graphite layer is 0.025-0.25 mm, and the thickness of the graphene layer is 0.01-0.025 mm.

Citation Information

Patent Citations

  • Preparation method of graphite film / graphene composite film

    CN107311659A

  • High-thermal-conductivity graphene-based composite film and preparation method thereof

    CN108658615A

  • Double-sided graphene heat dissipation film and preparation method

    CN111526695A

  • Graphene heat dissipation film and preparation method thereof

    CN112969355A